ENSAYO DE INTERPRETACION BOTANICA DEL LIBRO X DE LA HISTORIA DE SAHAGUN - RIVERA M, IRENE (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1941)
The results are given of the systematic and statistical studies on Glosso-phaga s soricina, including morph description and calculations of the parameters of lineal measurements, with their respective standard errors, coefficients of symmetry, correlati
ANS INST BIOL
Keywords: ENSAYO, INTERPRETACION BOTANICA, LIBRO X, HISTORIA, SAHAGUN; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL